Empirical studies on economics of innovation, public economics and management : procceedings of the 18th Eurasia Business and Economics Society Conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Can, Ugur (Springer, 2017)
This volume presents selected papers from the 18th Eurasia Business and Economics Society (EBES) Conference, with major emphasis placed on highlighting the latest research developments in the economics of innovation, public economics, and management. The articles in the volume also address more specialized topics such as luxury fashion, weather derivatives, health management, islamic bonds, and life satisfaction, among others. The majority of the articles focus on phenomena observed in the Middle East and North Africa (MENA) region and South Asia, representing a unique contribution to understanding contemporary research challenges from a different perspective.
Keywords: Economics -- Congresses.; Technological innovations -- Economic aspects -- Congresses.; Management -- Congresses.; Business -- Congresses.; elektronické knihy; electronic books